SYNTHESIS AND CHARACTERIZATION OF GELATIN-CHITOSAN NANOCOMPOSITE TO EXPLORE THE POSSIBLE USE AS DRUG DELIVERY VEHICLE - Sahoo, Rashmirekha; Sahoo, Soumendra; Nayak, Padma Lochan. (European Scientific Journal, ESJ, 2013)
We prepared hybrid nano-composites by blending chitosan-Gelatin with Cloisite 30B in aqueous solution. These composites were characterized by using FTIR, SEM and XRD analysis. Various groups present in the chitosan-Gelatin blend were monitored from FTIR spectra. The morphology, homogeneity and crystallinity of the blends were analyzed from SEM and XRD data. The results indicated that an intercalated or partially exfoliated nano-composite could be achieved, and the properties of the composite were significantly improved.